2017
DOI: 10.1515/crebss-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

The long-run impact of personal income taxation on economic development: Evidence from Croatia

Abstract: Since the endogenous growth model appeared in the economic theory, taxation has been considered as one of the key determinants of the economic growth. In the public finance theory, taxation is considered to have a negative impact on economic growth, which is explained by implications of tax revenues distortions on the economic activity. This assumption has been investigated by many empirical studies. The aim of this paper is to analyse the impact of personal income taxation on economic conditions in Croatia in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
1
18
0
2
Order By: Relevance
“…Ever since the formulation of the endogenous model, the impact of taxation on economic growth is interesting both for scientists and economic policymakers. For example, Palić et al (2017b) found that an increase in personal income taxation in Croatia statistically significantly decreases economic growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ever since the formulation of the endogenous model, the impact of taxation on economic growth is interesting both for scientists and economic policymakers. For example, Palić et al (2017b) found that an increase in personal income taxation in Croatia statistically significantly decreases economic growth.…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess the long-run impact of selected labor market variables on personal income taxation in FB&H, the Johansen's approach to cointegration is used. It is important to note that long-run equilibrium in econometric terms does not refer to market equilibrium, but to the long-run relationship of non-stationary variables (Palić, 2017, Palić et al, 2017b.…”
Section: Methodsmentioning
confidence: 99%
“…Budu i da se podaci o bruto doma em proizvodu objavljuju tromjese no, a indeksi industrijske proizvodnje mjese no, takva aproksimacija esto je korištena u ekonometrijskim istraživanjima s ciljem o uvanja stupnjeva slobode i pouzdanosti rezultata analize. Pri ispitivanju u inka indirektnog poreza na ekonomsku aktivnost u Hrvatskoj takvu aproksimaciju koriste Pali et al (2017). Pla e u javnom sektoru odre ene su prema NACE statisti koj klasiÞ kaciji gospodarskih aktivnosti u Europskoj zajednici (Eurostat, 2008.).…”
Section: Podaci I Modelunclassified
“…) pomo u empirijske analize zaklju uju da direktni porezi, posebno porez na dohodak i doprinosi, imaju dugotrajno negativan i snažan u inak na kretanje BDP-a u Hrvatskoj, dok pozitivne u inke indirektnih poreza treba promatrati s dozom opreza. Tako er, Pali et al (2017. ) empirijski potvr uju kako porez na dohodak u Hrvatskoj ima signiÞ kantan negativan u inak na ekonomski rast u dugom roku.…”
Section: Ispitivanje Postojanja Kointegracije I Analiza Modela Dugog unclassified
“…The development of endogenous growth model has included the effect of taxes on economic growth which depends on the structure of tax system (Palić et al 2017). In public finance, dominant opinion is that taxes have a negative effect on economic growth.…”
Section: Introductionmentioning
confidence: 99%